Psychological and pedagogical prevention of teachers ' emotional burnout - Аnastasiya V. Dolgopolova; Anastasiya M. Manukhina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper presents an analysis of the phenomenon of teachers emotional burnout. The relevance of the study is noted in connection with a large number of stressful factors in the professional activity of teachers. The symptoms of emotional burnout are considered. The reasons and factors that influence the formation and development of emotional burnout are highlighted. The emergence and development of emotional burnout is individual and depends on both external conditions and internal characteristics of the teacher's personality. The result of emotional burnout is deformation, when the protective mechanisms do not cope and the process of destruction of the personality is started.The content of psychological and pedagogical prevention of emotional burnout of teachers is determined. The main goals of psychological and pedagogical prevention of emotional burnout of teachers are following: awareness and understanding of professional motivation, development of positive self-attitude, increase of autopsychological competence, regulation of emotional state through understanding and acceptance of the entire repertoire of their own emotions, actualization of the value of their own physical and psychological health, development of effective communication skills, improvement of the psychological climate in the team.The results of the study of the dynamics of manifestations of emotional burnout during the implementation of a cycle of classes on psychological and pedagogical prevention of emotional burnout of teachers are presented. The content of the classes was aimed at updating the value of physical and mental health, increased levels of autopsychological competence of teachers, the development of positive self, learning of self-regulation of emotional state through the understanding and acceptance of the entire repertoire of own emotions, development of effective communication skills, improvement of the psychological climate in the team. Based on the results of repeated diagnostics, the conclusion is made about the effectiveness of the conducted cycle of classes, which can be used in the practice of teachers-psychologists of any educational institutions.